Growth and Flavonoids Content of Black Rice (Oryza sativa L. indica) with Compost Tea of Oyster Mushroom Waste - Khoerunnisa Khoerunnisa; Regata Ringga Hanessa Putry; Salma Aulia Salsabila; Mochammad Rezky Darmawan; Yasinta Nahdatulia; Iman Budisantoso (Caraka Tani: Journal of Sustainable Agriculture, 2022)
The flavonoid compounds in black rice (Oryza sativa L. indica) are very important for health, they serve, for instance, as antioxidants and anticancer. Giving compost tea of oyster mushroom waste (COMW) can increase plant growth and flavonoid content to black rice. This research aims to determine the effectiveness of COMW to increase the growth and flavonoid content of black rice. This experiment using completely randomized design with single factor of five COMW concentrations, four replicates respectively. The COMW was given at five different concentrations (0, 25, 35, 45 and 55%) from 25 to 45 days after planting. Parameters observed including plant height, fresh and dry weight of plants, fresh and dry weight of roots, fresh weight of grain, fresh and dry weight of total and flavonoid content. The results showed that COMW significantly increased black rice growth, the best growth was obtained by the concentration of 45% and the highest flavonoid content is by 35% concentration. No significant effect on crown height and canopy dry weight. There were significant effects on root fresh weight, shoot fresh weight, grain fresh weight, total fresh weight, root dry weight, dry weight grain, total dry weight and increased levels of flavonoids in black rice. From the research, it can be concluded that COMW increased both growth and flavonoids content of black rice.